2016
DOI: 10.1103/physrevfluids.1.074401
|View full text |Cite
|
Sign up to set email alerts
|

Near field development of artificially generated high Reynolds number turbulent boundary layers

Abstract: Particle image velocimetry (PIV) is conducted in the near field of two distinct wall-mounted trips for the artificial generation of a high Reynolds number turbulent boundary layer. The first of these trips consists of high aspect ratio obstacles which are supposed to minimize the influence of their wakes on the near-wall region, contrasting with low aspect ratio trips which would enhance this influence.A comprehensive study involving flow description, turbulent/non-turbulent interface detection, a low order mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…A possible explanation could be related to the large number of wakes generated by the numerous bars of different sizes that this geometry presents close to the wall (ŷ < 0.3, figure 2.3). These wakes generate a highly turbulent fluid which would undoubtedly improve the mixing of the outer and inner regions thus potentially increasing the fluctuating level in the inner region; a similar effect has been reported for over-tripped boundary layers downstream of blunt obstacles generating large recirculation regions (Rodríguez-López et al, 2016b). Another possible explanation could be that the outer, highly energetic, fluid is seen as a different boundary condition for the inner region which, contrary to the natural case, enhances the level of the fluctuations of the near-wall region without changing its characteristic frequency.…”
Section: Fluctuating Shear Stress τmentioning
confidence: 89%
See 1 more Smart Citation
“…A possible explanation could be related to the large number of wakes generated by the numerous bars of different sizes that this geometry presents close to the wall (ŷ < 0.3, figure 2.3). These wakes generate a highly turbulent fluid which would undoubtedly improve the mixing of the outer and inner regions thus potentially increasing the fluctuating level in the inner region; a similar effect has been reported for over-tripped boundary layers downstream of blunt obstacles generating large recirculation regions (Rodríguez-López et al, 2016b). Another possible explanation could be that the outer, highly energetic, fluid is seen as a different boundary condition for the inner region which, contrary to the natural case, enhances the level of the fluctuations of the near-wall region without changing its characteristic frequency.…”
Section: Fluctuating Shear Stress τmentioning
confidence: 89%
“…These facts make it difficult to extrapolate any clear trend in the vicinity of the grids. Moreover, different grids may generate distinct turbulent structures which may influence the near wall region differently (Rodríguez-López et al, 2016b). Further downstream, the boundary layer growth appears to be uniform and more solid conclusions can be drawn.…”
Section: Fluctuating Shear Stress τmentioning
confidence: 90%
“…In order to explore the causes of the two different boundary layer thickening mechanisms downstream of the cylinder and sawtooth trips Rodríguez-López et al (28) conducted a particle image velocimetry (PIV) study immediately downstream of the trips. They reported the importance of the dynamics of the turbulent/nonturbulent interface (TNTI) to determining which mechanism, wall-driven or wake-driven, prevailed.…”
Section: Introductionmentioning
confidence: 99%
“…These motions transport fluid across the entire wall-normal extent of the flow and thus disrupt the near-wall motions from their canonical state. Rodríguez-López et al (28) concluded by postulating three distinct geometrical parameters that would govern whether the wall-driven or wake-driven mechanism would prevail. These were the aspect ratio of the trips, the overall blockage ratio and the blockage at the wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation